Risk Management in the Pharmaceutical Industry Supply Chain at the Pharmaceutical Wholesaler Level - Evi, Sylvia; Sriwidodo, Sriwidodo; Masrahman, Roestan (Universitas Padjadjaran (Unpad), 2025)
The pharmaceutical industry in Indonesia faces several challenges in risk management, particularly in stakeholder management, which includes the government, healthcare providers, distributors, and the public. The complexity of regulations, market fluctuations, and changes in healthcare policies necessitate the implementation of effective risk management strategies in interactions with stakeholders. This study aims to analyze the implementation of risk management in stakeholder management within Indonesia’s pharmaceutical industry, identify key risks that may impact business sustainability, and evaluate the mitigation approaches employed. A qualitative case study, incorporating in-depth interviews with key industry stakeholders, revealed that the primary risks include regulatory uncertainty, supply chain disruptions, and challenges in stakeholder communication and compliance. Effective mitigation strategies involve the adoption of adaptive compliance systems, strengthened communication and collaboration with regulators, and digitization of supply chains to enhance transparency and efficiency. This study underscores the importance of a risk-based approach in stakeholder management to ensure the sustainability and competitiveness of Indonesia’s pharmaceutical industry.